Talaromyces systylus, a new synnematous species from Argentinean semi-arid soil - Romero, Stella Maris; Romero, Andrea Irene; Barrera, Viviana Andrea; Comerio, Ricardo Mario (2017)
The discovery of an interesting new synnematous Talaromyces species from Argentinean semi-arid soil has enlarged the number of synnema-producing species. Talaromyces systylus sp. nov. is characterized by the production of indeterminate synnemata on Malt Extract Agar and coarsely rough-walled, globose conidia and conidial chains arranged in columns. The optimal growing temperature was 30°C. Talaromyces systylus was compared with other related species phylogenetically based on ITS, BenA and CaM markers.